A multilevel dynamic model for documenting, reactivating and preserving interactive multimedia art - Fiordelmondo, Alessandro; Russo, Alessandro; Pizzato, Mattia; Zecchinato, Luca; Canazza, Sergio (Frontiers in Signal Processing, 2023)
Preserving interactive multimedia artworks is a challenging research field due to their complex nature and technological obsolescence. Established preservation strategies are inadequate since they do not cover the complex relations between analogue and digital components, their short life expectancies, and the experience produced when the artworks are activated. The existence of many projects in this research area highlights the urgency to create a preservation practice focused on the new multimedia art forms. The paper introduces the Multilevel Dynamic Preservation (MDP) model, developed at the Centro di Sonologia Computazionale (CSC) of the University of Padova, which aims to preserve multimedia artworks through different levels of information (about the components, their relationship and the activated experiences) through various exhibitions and thus as a process or a dynamic object. The model has been developed through several case studies. This paper reports a specific and complex one: the “hybrid reactivation” of the Il caos delle sfere, a 1999 interactive installation by Italian composer Carlo De Pirro. The entire reactivation process aims at preserving its identity, rather than simply replicating the original installation, and consists of both the replacement of old and non-functioning components components (“adaptive/update approach”) and the reactivation of original parts (“purist approach“)-hence the name “hybrid reactivation”. Through this case study, it was possible to test and optimize the model in all aspects: from collecting old documentation and using it for reactivation to creating new documentation and archiving the entire artwork. The model allows us to preserve the artwork as a process of change, minimizing the loss of information about previous versions. Most importantly, it lets us rethink the concept of the authenticity of interactive multimedia art, shifting the focus from materiality to the experience and function that artworks activate. The model avoids recording both the last reactivation and the first exhibition as authentic. It records the process of transformation between reactivations. It is through this process that the authenticity of the artwork can be inferred.